Greenhouse gas emissions from a pilot-scale small decentralized sewage treatment: anaerobic filter + constructed wetland (2016)
(Eng) Greenhouse gases such as CH4, CO2 and N2O were measured in a Small-Decentralized Sewage Treatment (SDST). The system consisted of an up-flow anaerobic filter (UAF) and two constructed wetlands (CWs) operating in parallel. The constructed wetlands were planted with Heliconia sp L. (HCW) y C. papyrus. (PCW). The results showed that GHG average (daytime and nighttime) emissions from UAF (1.8 - 8.9 g.m-2.d-1 CO2; 8.3 y 45 g.m-2.d-1 CH4) were higher than measured in HCW (-5.1 y 5.5 gCO2.m-2.d-1; 10 y 556 mgCH4.m-2.d-1; -4 and 40 mgN2O.m- 2.d-1) and PCW (-0.85 to 6.5 gCO2.m-2.d-1; 2.3 and 1590 mgCH4.m-2.d-1; -7 y 12 mgN2O.m-2.d-1). A statistical test showed that there were not significant differences between GHG flux (daytime-nigh-time) measured in HCW and PCW (p<0.05). Further, the variations on GHG could be explained by water temperature, photoperiod, NH4+ and dissolved oxygen mainly. High temperature stimulates GHG production. Photoperiod in CWS increased CO2 and CH4 sequestration. Further, the presence of dissolved oxygen and NH4+ influenced N2O production. Overall, in this study was determined that SDST act like a net source of GHG emitting 0.7 kg CO2eq. Kg CODrem..